THU0237 Impact of recurrent ischemic digital ulcers on hand disability in systemic sclerosis –. (23rd January 2014) - Mouthon, L.; Carpentier, P.; Khau Van Kien, A.; Clerson, P.; Maillard, H.; Hachulla, E.; Frances, C.; Diot, E.; Lok, C.; Puzenat, E.; Sparsa, A.; Bérezné, A.; et al.
Abstract : Background: Ischemic digital ulcers (DU) are a common complication of systemic sclerosis (SSc). Objectives: To evaluate the impact of recurrent DU on hand disability in a prospective, longitudinal, observational study of 24 months. Methods: Patients fulfilled ACR or Leroy-Medsger criteria for SSc, experienced at least one DU during the previous year with or without active DU at inclusion, and were eligible for bosentan therapy. Data were collected on SSc, characteristics of past and present DU, modified Rodnan skin score, factors influencing hand function and mobility, disability scores (Cochin hand function scale - CHFS, health assessment questionnaire disability index - HAQ-DI), and quality of life (SF36). Results: 217 patients were included between October 2009 and March 2011 in 50 centers. The interim analysis includes 184 patients (128 women). Mean age was 43±15 years at diagnosis of SSc and 53±15 years at inclusion. SSc was diffuse in 44% of patients and Raynaud's phenomenon (RP) started 14±12 years before inclusion. 11% of patients had pulmonary arterial hypertension. Mean Rodnan score was 14.3±8.8. Time elapsed since the first DU was 6±7 years. In 47% of patients, DU was an early complication (first non-RP sign) and 59% had recurrent DU. Sequelae of DU included loss of substance (62%), autoamputation (8%), and surgical amputation (10%). Complications were infection (8%), gangrene (5%), and osteitis (2%). 54% of patients had at least one active DU at inclusion. In these patients, the mean number of DU was 2.3±1.9; 54% had more than one DU, 37% had both hands involved, and on average 2.2±1.7 fingers were affected. 21% of cases had at least one extended DU (>1cm). Concomitant mechanical ulcers were localized at the dorsal face of fingers (19%), bony reliefs (13%), or calcinosis (1%). DU were painful (visual analogue scale, 6.18±2.56 vs. 2.49±2.56 without DU) and disabling, involving the dominant hand in 72% of patients. DU worsened hand disability (median CHFS, 42 with active DU vs. 26 without DU, p<0.0001), HAQ-DI, and affected SF36. Other factors contributing independently to hand disability were reduced proximal or distal interphalangeal joint mobility of at least one finger (56% and 66% of patients, respectively) and retraction of flexor tendons (45%). Conclusions: DU represent an early complication of SSc. They are painful, affecting often multiple fingers and both hands. In patients with SSc, DU are significantly associated with hand disability. Prospective follow-up at two years will allow to further elucidate the specific role that DU episodes play in the disability of these patients. Disclosure of Interest: L. Mouthon Consultant for: Lilly, Actelion France, GSK, Pfizer, P. Carpentier Consultant for: Actelion, A. Khau Van Kien: None Declared, P. Clerson: None Declared, H. Maillard: None Declared, E. Hachulla Consultant for: Actelion, GSK, Pfizer, C. Frances: None Declared, E. Diot: None Declared, C. Lok Consultant for: Actelion, E. Puzenat Consultant for: Actelion, A. Sparsa Consultant for: Actelion, A. Bérezné: None Declared, V. Gressin Employee of: Actelion France, M.-A. Richard Consultant for: Actelion